SMART DEFENSE SYSTEMS FOR MARITIME SECURITY: PRIORITIES AND CRITERIA FOR NATIONAL DEFENSE DEVELOPMENT - Wiratama, Eska Yosep; Wirjodirdjo, Budisantoso; Santoso, Yoyok Nurkarya; Sahiri, Erpan (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2023)
Force development is directed at meeting the needs of the 2020-2044 National Defense System Development The Indonesian Navy is capable of upholding sovereignty and law in the Indonesian National Jurisdiction area which is guided by the development direction of meeting the 2020-2044 national defense system development needs of the defense of large islands and clusters strategic islands and the surrounding waters within the framework of the Archipelago Marine Defense Strategy and the Indonesian Maritime Defense Strategy. Fulfilling the Needs for the Development of the National Defense System for 2020-2044 the required forces of the Indonesian Navy consist of KRI, aircraft, bases, The concept and strategy of national defense at sea that has been carried out above proves that the concept of national defense at sea has been implemented, and is in accordance with the threats faced. The concept and strategy of national defense at sea is also supported by relevant war strategy theories. The increasingly dynamic spectrum of threats caused by Indonesia's geographical constellation and developments in the global and regional strategic environment have been able to be answered by the national defense strategy as outlined in both national legislation and national defense doctrine. So in this research we need a strategic structure for the strength of the sea dimension that is able to carry out the defense of the archipelago to face every threat both actual and potential and will provide scientific studies by creating a dynamic system model of the SPLN smart defense to support the duties of the Indonesian Navy. In this study, the authors will use the Delphi method to determine the criteria for smart defense that have an effect on SPLN, then use Fuzzy Weighting to determine priorities in the development of smart defense systems. Keywords:Smart Defense, Delphi, Fuzzy Weighting.